(untitled) (The Review of Diabetic Studies, 2024)
Background: Collaboration between physicians and nurses is essential to healthcare delivery and is associated with high-quality patient care, greater patient satisfaction, and better health outcomes. Hence, it is imperative that doctors and nurses have a particular set of inter-professional collaboration skills. The study aimed to identify nurses’ perceptions of professional nursing autonomy and the relationship between nurse-physician collaboration. Method: A descriptive correlational design was utilized to conduct this study. Setting: This study conducted at critical care units at Jeddah Hospital, KSA. Study sample: a convenient sample contains 277 nurses. Tool: Two tools were used for data collection, the first tool: Nurse and physician collaboration scale, the second tool: Professional nursing autonomy scale. Results: Showed that more than third (39, 4%) of nurses had low perception level regarding nurse physician collaboration and more than two fifth (46, 9%) of them had low perception level about professional nursing autonomy. The Conclusion: Overall nurses’ perceptions of nurse/physician collaboration and overall professional nursing autonomy were positively correlated in a highly statistically significant way. According to the study’s recommendations, more research is required to fully understand the significant obstacles to inter-professional collaboration and the detrimental effects it has.